Diversificación de la Cartera de Activos de la Banca Múltiple en el Perú: 2001-2011 - Cortez Cortez, Gaby (2013)
Diversification of bank operations in the most economic sectors , still has space allocated for Classical Financial Theory, which suggests that diversification may be a way to reduce the risk of a portfolio of assets (Haugen, 2001) associated with higher profits and lower operating costs. During the period 2001-2011 the banks that are active in the banking market in Peru have shown a high degree of diversification expressed in the majority stake in a number of economic sectors, also associated with higher rates of return on capital expressed through ratio ROE (Return on Equity)